The Impact of Cervical Sagittal Slope on Postural Oscillation and Balance - Akay, Hilal; Demirel, Adnan; Berk, Ejder; Nacitarhan, Vedat; Baykara, Murat (Kahramanmaras Sutcu Imam University, 2022)
Aim: Static balance and postural oscillation can be affected by different diseases. The aim of this study was to investigate balance disorders with clinical tests and stabilometric measurements in individuals with cervical lordosis loss or cervical kyphosis and to compare the balance state with cervical lordosis individuals. Material and method: In our study, 102 patients, with cervical lateral radiographs and met criteria for inclusion into the study, who applied to the physical medicine and rehabilitation polyclinic within the last 6 months were evaluated. Patients were divided into 4 groups according to the cervical sagittal slope angles calculated based on the Cobb method. Stabilometric measurements of the patients were performed in 8 different positions (Table 1). In addition, the berg balance scale (BBS) and the activity-specific balance confidence scale (ABC) scores were calculated and the timed up and go test (TUG), the four square step test (FSST) and the functional reach test (FRT) were performed. Statistical significance was accepted as p <0,05 in all statistical evaluations. Findings: Statistically significant differences were found in the head neutral position (NC) mediolateral oscillation rate, NC mediolateral total oscillation amount, NC anteroposterior oscillation rate, NC anteroposterior total oscillation amount, NC vectorial maximum oscillation amount, NC vectorial total oscillation amount, head in right rotation (HR) anteroposterior maximum oscillation amount, HR anteroposterior oscillation rate, HR anteroposterior total oscillation amount and eyes closed on sponge, head in neutral position (PC) anteroposterior maximum oscillation amount from the stabilometric measurements of the patients participating in the study. There was no significant difference between the groups in terms of BBS score, ABC score, TUG and FSST score and FRT. Conclusion: According to the results of this study, while there were significant differences in terms of some posturographic parameters among the patients grouped according to the cervical sagittal slope angles, there was no difference between the groups in terms of some parameters. This result suggests that cervical sagittal slope gradually affects some components of postural performance from lordosis to kyphosis, however, not all components were affected by that.

Amaç: Statik denge ve postüral salınım farklı hastalıklardan etkilenebilir. Bu çalışmanın amacı; servikal lordoz kaybı ya da servikal kifoz olan bireylerde klinik testler ve stabilometrik ölçümler ile denge bozukluğunu araştırmak ve servikal lordozu olan bireylerle denge durumunu karşılaştırmaktır. Gereç ve Yöntem: Çalışmamızda son 6 ay içinde Fiziksel Tıp ve Rehabilitasyon polikliniğine başvuran, servikal lateral grafisi çekilmiş olan ve araştırmaya alınma kriterlerine uyan 102 hasta değerlendirildi. Hastalar Cobb metoduna göre hesaplanan servikal sagittal eğim açılarına göre 4 gruba ayrıldı. Hastaların 8 farklı pozisyonda stabilometrik ölçümleri yapıldı. Ayrıca berg denge skalası (BDS) ve aktiviteye özgü denge güvenlik skalası (AÖDGS) skorları hesaplanıp, zamanlı ayağa kalkma yürüme testi (ZAKYT), dört kare adımlama testi (DKAT) ve fonksiyonel uzanma testi (FUT) yapıldı. İstatistiksel tüm değerlendirmelerde anlamlılık düzeyi p<0,05 olarak kabul edildi. Bulgular: Çalışmaya katılan hastaların stabilometrik ölçümlerinden NC mediolateral salınım hızı, NC mediolateral toplam salınım miktarı, NC anteroposterior salınım hızı, NC anteroposterior toplam salınım miktarı, NC vektöriyel maximum salınım miktarı, NC vektöriyel toplam salınım miktarı, HR anteroposterior maksimum salınım miktarı, HR anteroposterior salınım hızı, HR anteroposterior toplam salınım miktarı ve PC anteroposterior maksimum salınım miktarı bakımından istatistiksel olarak anlamlı fark saptandı (p<0.05)(Tablo 1). BDT skoru, AÖDGS skoru, ZAKYT ve DKAT süresi ve FUT açısından ise gruplar arasında anlamlı fark yoktu. Sonuç: Bu çalışmanın sonuçlarına göre servikal sagittal eğim açılarına göre gruplandırılan hastalar arasında bazı postürografik parametreler açısından anlamlı farklar tespit edilirken, bazıları açısından gruplar arasında fark bulunamamıştır. Bu sonuç servikal sagittal eğimin lordozdan kifoza doğru gittikçe postüral performansın bazı komponentlerini olumsuz yönde etkilediğini ancak tüm komponentlerini etkilemediğini düşündürmektedir.
Servikal Sagital Eğimin Postüral Salınım ve Denge Üzerine Etkisi
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi